Rapporteurs' Report - Abd. Hadi, Annur Thahirah; Maruthaveeran, Vijayalatchumy (2015)
The Pre-Conference Workshop was held on 13 September 2015 at Pullman Kuala Lumpur, Bangsar with the same Social Media in the Library. It was facilitated by Mr. Ahmad Faizar Jaafar and Ms. Yusrina Abu Bakar and the participants were from various libraries throughout Malaysia.